Retraction Note: Constraining Neutron-Star Matter — Combination of heavy-ion experiments, astronomy and theory - Le Fèvre Arnaud; Huth Sabrina; Pang Peter T. H.; Tews Ingo; Dietrich Tim; Schwenk Achim; Trautmann Wolfgang; Agarwal Kshitij; Bulla Mattia; Coughlin Michael W.; Van Den Broeck Chris (EPJ Web of Conferences, 2023)
This paper has been formally retracted because it has been accidentally published twice in the same volume. Request approved by the proceedings Editor and the Publisher on January 29, 2024.